Controversies in Alzheimer’s disease drug development - Cummings, Jeffrey L. (2008)
Understanding of the pathophysiological basis of Alzheimer’s disease (AD) is increasing rapidly and a variety of potential treatment modalities have emerged based on these improved mechanistic insights. The optimal way of proceeding with disease-modifying drug development remains to be clarified and controversies have emerged regarding the definition of Alzheimer’s disease, the participation of mild cognitive impairment patients in clinical trials, the definition of disease modification, the potential impediments to satisfaction from patients receiving disease-modifying therapy, the importance of add-on therapy with symptomatic agents, the optimal clinical trial design to demonstrate disease modification, the best means of minimizing time spent in Phase II of drug development, the potential role of adaptive designs in clinical trials, the use of enrichment designs in clinical trials, the role of biomarkers in clinical trials, the treatment of advanced patients with disease-modifying agents, and distinctions between disease modification and disease prevention. The questions surrounding these issues must be resolved as disease-modifying therapies for AD are advanced. These controversies are framed and potential directions towards resolution described.